Valproate and Risk of Fracture in Rett Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
The association between fracture risk and commonly used antiepileptic drugs (AEDs) in 233 cases of Rett syndrome was investigated by researchers at medical centers in Australia.